PENGGUNAAN PAKAN LENGKAP BERBASIS TEBON JAGUNG TERHADAP KECERNAAN SERAT KASAR DAN BAHAN EKSTRAK TANPA NITROGEN SAPI FRIES HOLLAND - Binol, Didin; Tuturoong, R.A.V.; Moningkey, S.A.E; Rumambi, A. (ZOOTEC, 2020)
THE USE OF A COMPLETE FEED BASED ON CORN FORAGE ON THE DIGESTIBILITY OF CRUDE FIBER AND NITROGEN FREE EXTRACT OF THE FRIES HOLLAND DAIRY COWS. This study aims to determine of the use of complete feed based on corn forage on the digestibility of crude fiber and nitrogen free-extract (NFE) of the Fries Holland (FH) dairy cows. This research used 14 dairy cows aged 7-8 years with a bodyweight of 300-400 kg. This study used an experimental method with t-test analysis (unequal diversity) consisting of 2 treatments with 7 replications. This study was arranged in two treatment groups according to t-test (assuming unequal varience). They consisted of Ra = 70% corn forage + 30% concentrate and Rb = 35% corn forage + 35% king grass + 30% concentrate. The variables observed were crude fiber consumption, NFE consumption, crude fiber digestibility and NFE digestibility. T Test analysis results showed that the consumption of crude fiber treatment of Ra (2.07 kg/head/day) was not significantly different (P>0.05) with Rb treatment (2.10 kg/head/day) while NFE consumption showed no significant difference (P>0.05) between Ra (3.36 kg/head/day) and Rb (3.46 kg/head/day). The digestibility of crude fiber showed a very significant difference (P<0.01) between Ra (70.31%) and Rb (78.15%) while NFE digestibility showed no significant difference (P>0.05) between Ra (87.97%) and Rb (90.28%). Based on the results of this study it can be concluded that feeding with concentrate of 30%, corn forage of 35% and king grass of 35% has better in increasing digestibility of crude fiber than just consisting of concentrate of 30% and corn forage of 70% in dairy cows (FH).Keywords: digestibility, crude fiber, NFE, Fries Holland cows